2005
DOI: 10.1063/1.2130526
|View full text |Cite
|
Sign up to set email alerts
|

Space-charge-limited bipolar flow in a nano-gap

Abstract: This paper presents a quantum model of space-charge limited (SCL) bipolar flow in a nano-sized planar gap, including the effects of electron tunneling and exchange-correlation. It is found that the classical scaling of the SCL bipolar flow is no longer valid when the gap spacing D is comparable or smaller than the electron’s de Broglie wavelength at gap voltage Vg. The classical value of the SCL bipolar electron flow is greatly enhanced due to the electron tunneling through the space-charge electric potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The classical value of the SCL bipolar electron flow is also greatly enhanced due to the electron tunneling through the space charge field created by both the electrons and ions, and it is no longer equal to the classical limit which is 1.86 times that of the classical CL law. 158 To realize the quantum SCL current in a nano gap, there were also studies to model the transition from field emission to SCL current in a nano gap at different conditions. 159 By assuming the field emission to be governed by the Fowler-Nordheim (FN) law, 160 it was found that the emission current can go beyond the classical CL law to reach the quantum CL law for a nanometer gap in the high current regime.…”
Section: B Quantum Scl Scalingmentioning
confidence: 99%
“…The classical value of the SCL bipolar electron flow is also greatly enhanced due to the electron tunneling through the space charge field created by both the electrons and ions, and it is no longer equal to the classical limit which is 1.86 times that of the classical CL law. 158 To realize the quantum SCL current in a nano gap, there were also studies to model the transition from field emission to SCL current in a nano gap at different conditions. 159 By assuming the field emission to be governed by the Fowler-Nordheim (FN) law, 160 it was found that the emission current can go beyond the classical CL law to reach the quantum CL law for a nanometer gap in the high current regime.…”
Section: B Quantum Scl Scalingmentioning
confidence: 99%
“…20 The classical CL law has also been extended to quantum regime to include the quantum effects on the dynamic of SCL electron flows in a nanogap. [21][22][23][24][25] The shortpulse CL law has been also studied in classical, 26,27 quantum, and weakly relativistic 28 regimes. Recent developments of the CL law in multidimensional models and quantum models can be found in two review papers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This maximum value arises because the space charge in the diode presents a potential barrier to the incident electrons. In the research of vacuum electronics on a scale down to a few or tens of nanometers, the quantum effects should be considered and cannot be neglected [1][2][3][4][5]. In a previous work of Lau et al…”
mentioning
confidence: 99%